Serotype-Independent Protection Against Invasive Pneumococcal Infections Conferred by Live Vaccine With lgt Deletion - Jang, A-Yeung; Ahn, Ki Bum; Zhi, Yong; Ji, Hyun-Jung; Zhang, Jing; Han, Seung Hyun; Guo, Huichen; Lim, Sangyong; Song, Joon Yong; Lim, Jae Hyang; Seo, Ho Seong (Frontiers in Immunology, 2019)
Streptococcus pneumoniae is the most common respiratory bacterial pathogen among cases of community-acquired infection in young children, older adults, and individuals with underlying medical conditions. Although capsular polysaccharide-based pneumococcal vaccines have contributed to significant decrease in invasive pneumococcal infections, these vaccines have some limitations, including limited serotype coverage, lack of effective mucosal antibody responses, and high costs. In this study, we investigated the safety and immunogenicity of a live, whole-cell pneumococcal vaccine constructed by deleting the gene for prolipoprotein diacylglyceryl transferase (lgt) from the encapsulated pneumococcal strain TIGR4 (TIGR4Δlgt) for protection against heterologous pneumococcal strains. Pneumococcal strain TIGR4 was successfully attenuated by deletion of lgt, resulting in the loss of inflammatory activity and virulence. TIGR4Δlgt colonized the nasopharynx long enough to induce strong mucosal IgA and IgG2b-dominant systemic antibody responses that were cross-reactive to heterologous pneumococcal serotypes. Finally, intranasal immunization with TIGR4Δlgt provided serotype-independent protection against pneumococcal challenge in mice. Taken together, our results suggest that TIGR4Δlgt is an avirulent and attractive broad-spectrum pneumococcal vaccine candidate. More broadly, we assert that modulation of such “master” metabolic genes represents an emerging strategy for developing more effective vaccines against numerous infectious agents.